1999
DOI: 10.1002/(sici)1097-0177(199912)216:4/5<320::aid-dvdy2>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BMP-7 on mouse tooth mesenchyme and chick mandibular mesenchyme

Abstract: BMP‐7 is a member of the BMP family of signaling molecules that are thought to play key roles in mediating inductive events during embryogenesis. In the present study the possible roles of BMP‐7 in mediating inductive events during the initiation phase of odontogenesis and mandibular morphogenesis were investigated. To do so, we have examined the effects of agarose beads soaked in recombinant BMP‐7 on E11 mouse molar‐forming mesenchyme and stage 23 chick mandibular mesenchyme, and analyzed the patterns of expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 98 publications
(139 reference statements)
3
48
1
Order By: Relevance
“…The colocalization of the BMP downstream gene Msx1 and the proliferation activity in the FNM are consistent with the notion that BMP signalling is critical for beak morphogenesis. Our data are consistent with the previous studies that demonstrated that ectopic application of BMP protein-coated beads can activate MSXs gene expression in the developing facial primordia (Barlow and Francis-West, 1997;Wang et al, 1999b;Ashique et al, 2002a;Mina et al, 2002).…”
Section: Msx Genes Are Regulated By Bmp4 In Beak Prominencessupporting
confidence: 93%
“…The colocalization of the BMP downstream gene Msx1 and the proliferation activity in the FNM are consistent with the notion that BMP signalling is critical for beak morphogenesis. Our data are consistent with the previous studies that demonstrated that ectopic application of BMP protein-coated beads can activate MSXs gene expression in the developing facial primordia (Barlow and Francis-West, 1997;Wang et al, 1999b;Ashique et al, 2002a;Mina et al, 2002).…”
Section: Msx Genes Are Regulated By Bmp4 In Beak Prominencessupporting
confidence: 93%
“…Spatiotemporal changes in Bmp4 expression correlate with the timing of osteogenic tissue interactions in the mandible, and they corroborate other BMP gene expression studies (Barlow and Francis-West, 1997;Nonaka et al, 1999). The switch of Bmp4 expression from epithelium to mesenchyme during avian osteogenesis is similar to what has been observed during mouse odontogenesis, and to what has been shown for bone development (Vainio et al, 1993;Aberg et al, 1997;Barlow and Francis-West, 1997;Tucker et al, 1998b;Nonaka et al, 1999;Wang et al, 1999). For example, this expression transition does not occur in Msx1 mutant mice, and, ultimately, results in adontia and lower jaw deficiencies (Satokata and Maas, 1994;Chen et al, 1996).…”
Section: Mesenchyme Regulates Mesenchymal Bmp Signalingsupporting
confidence: 61%
“…The Msx1-induced Bmp4 from the dental mesenchyme instructs the overlying dental epithelium to form the enamel knot, which guides tooth morphogenesis [93,110]. After the cap stage, tooth development begest that Msx1 and Msx2 mediate the inductive effects of BMP7 on mandibular morphogenesis as well as the initiation phase of odontogenesis [94]. The induction of Ptc, a downstream target of Shh signaling, in the dental mesenchyme is contingent upon Msx1, which is coexpressed with Ptc [91].…”
Section: Regulation Of Msx1 and Msx2 Expression And Facial Patterningmentioning
confidence: 99%